Influência do método de fabricação no comportamento de fratura de coroas totalmente cerâmicas - Piccoli, Ana Carolina Antunes (2014)
In-Ceram Zirconia is an alumina-based zirconia-reinforced glassinfiltrated ceramic produced using two different techniques, slip-cast and CAD-CAM. Ceramics microstructure and fabrication methods are related to restorations mechanical performance. Thus, the objective of this study was to evaluate the influence of In-Ceram Zirconia’s fabrication method on the failure behavior of all-ceramic crowns. A glass fiber-reinforced composite die simulating a prosthetic preparation was used to produce the crowns. Two groups of crowns with In-Ceram Zirconia infrastructure (IE) were evaluated (n=30): IZC – IE produced with CAD/CAM technology and IZS – IE produced using slip-cast technique. IE were veneered with porcelain (Vita VM7) and cemented over the die with resin cement. Crowns were tested until failure using a universal testing machine with a compressive load being applied parallel to the crown long axis, with 1 mm/min cross -head speed, in 37º distilled water. Fractographic analysis was performed using a stereomicroscope. Data were statistically analyzed with student t test (α=0.05) and Weibull analysis. There was no significant differences between the experimental groups for the fracture load (p=0.481). Weibull modulus and characteristic strength were also similar among groups. For both groups, the failure mode was catastrophic failure involving IE and porcelain. It was concluded that both fabrication methods resulted in all-ceramic crowns with similar failure behavior and reliability.